RedDots: panetary masses in the GJ 1061 system from planet-planet interaction - Dreizler, Stefan; Jeffers, S. V.; Liebing, F.; Gorrini, P.; Haswell, C. A.; Gaidos, E.; Barnes, J. R.; Sordo, F. Del; Jones, H. R. A.; Rodríguez, E.; Tsapras, Yiannis (Astronomy and astrophysics, 2025)
GJ 1061 is a very nearby M star hosting three low-mass temperate planets detected from radial velocity variations. The close to 4:2:1 period commensurability of the planets, the available long-term monitoring of the system, and new very-high-precision radial velocity measurements from ESPRESSO enable the determination of masses from the planet-planet interaction. Using nested sampling we derived parameter distributions for a co-planar configuration. The three planets (Mb=1.07 ± 0.11 M⊕, Pb=3.2073 ± 0.0003 d; Mc=1.76 ± 0.13 M⊕, Pc = 6.6821 ± 0.0008 d; and Md=1.55 ± 0.17 M⊕, Pd=13.066 ± 0.002 d) are potentially all rocky with equilibrium temperatures between 360 and 240 K. This makes the GJ 1061 system one of the prime targets for future ground- or space-based instruments suitable for a direct detection of the planetary atmospheres.
Online verfügbar: 6. Juni 2025
Gesehen am 12.01.2026